Development and evaluation of a Chinese character educational board game for non-native learners / Lee Chai Chuen and Nor Azrina Mohd Yusof - Lee, Chai Chuen; Mohd Yusof, Nor Azrina (UiTM Cawangan Kedah, 2021)
There is no doubt that knowing Chinese gives graduates a competitive advantage. The ability to communicate fluently in Chinese has long been a requirement for Chinese employers, particularly those looking to do business in China's e-commerce market. Non-native learners must master four fundamental abilities in order to become literate in the Chinese language: listening, reading, writing, and speaking. Previous research has found that writing Chinese characters is frequently the most difficult task for both non-native and native learners. The issue arises during the process of learning Chinese characters and excessive use of gadgets, while online learning inspires both researchers to create a Chinese educational board game dubbed the LiSCReW Family Board Game (LiSCReW). LiSCReW is an acronym for Listen, Speak, Count, Read, and Write. The purpose of this study is (i) to develop and evaluate the effectiveness of the LiSCReW for learning Chinese characters; and (ii) to share non-native learners' perspectives and experiences while playing LiSCReW during a one-day exhibition at Universiti Teknologi MARA (UiTM) Johor Campus. To facilitate playtesting and evaluation of the board game, a total of 22 students from UiTM Johor were conveniently selected. The findings indicate that the LiSCReW board game is an effective educational tool for learning Chinese characters. The results show that respondents are more confident in recognising Chinese characters (90.9%), pronouncing Chinese characters (68.2%), reading Chinese characters (54.6%), and applying the Chinese characters they learned while Journal of Creative Practices in Language Learning and Teaching (CPLT) Volume 9, Number 2, 2021 playing LiSCReW to their Chinese test (77.2%). The findings can be used to guide future research into the empirical testing of Flow Theory's applicability among a large number of respondents.